2013
DOI: 10.1049/iet-com.2012.0428
|View full text |Cite
|
Sign up to set email alerts
|

Practical polar code construction over parallel channels

Abstract: Channel polarisation results are extended to the case of communications over parallel channels, where the channel state information is known to both the encoder and decoder. Given a set of parallel binary-input discrete memoryless channels (B-DMCs), by performing the channel polarising transformation over independent copies of these component channels, we obtain a second set of synthesised binary-input channels. Similar to the single-channel case, we prove that as the size of the transformation goes infinity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The selection of the repeated or punctured positions has strong impact on finite-length performance [12]. The best known universal solution is performing a bit-reversal permutation on the coded bit sequence, then repeating/puncturing |M − N | bits sequentially from the first, or in a reverse order from the last.…”
Section: B Rate-matching Schemes Of Polar Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the repeated or punctured positions has strong impact on finite-length performance [12]. The best known universal solution is performing a bit-reversal permutation on the coded bit sequence, then repeating/puncturing |M − N | bits sequentially from the first, or in a reverse order from the last.…”
Section: B Rate-matching Schemes Of Polar Codesmentioning
confidence: 99%
“…The channel reliabilities are changed after rate-matching, so the optimal active set A should be adjusted accordingly [12]. However, in HARQ procedure, there is no chance to change the set A once it is determined at the first transmission.…”
Section: B Rate-matching Schemes Of Polar Codesmentioning
confidence: 99%
“…It is shown that using larger generator matrices allows obtaining polar codes with flexible code lengths while maintaining an error performance comparable to that of the original construction. This is an efficient way to obtain polar codes of flexible code lengths and is comparable to the contribution of [11]. In [11], the authors propose the use of puncturing together with codes with length equal to the next power of 2 to obtain the desired code length.…”
Section: Introductionmentioning
confidence: 95%
“…This is an efficient way to obtain polar codes of flexible code lengths and is comparable to the contribution of [11]. In [11], the authors propose the use of puncturing together with codes with length equal to the next power of 2 to obtain the desired code length. This approach can be used in conjunction with the proposed approach to obtain codes of desired length with minimal use of puncturing by starting with a slightly larger block length (not necessarily the next power of 2) and puncturing the unnecessary symbols/channels.…”
Section: Introductionmentioning
confidence: 95%
“…The RCPP codes over AWGN channel are well studied in [7]. Given an AWGN channel and a specific RCPP code, the block error rate (BLER) can be accurately predicted under the framework of channel polarization over parallel channels [8]. The code construction and performance evaluation methods of RCPP codes are extended to the Rayleigh fading channels.…”
Section: Introductionmentioning
confidence: 99%